Electronics reliability methods for neutrinos telescopes: the KM3NeT case. (27th October 2021) - Colonges, S.; Real, D.; Calvo, D.; Musico, P.; Pellegini, G.; Jansweijer, P.; van Beveren, V.; Chiarusi, T.; Bozza, C.; Nicolau, C.; Díaz, A.
Abstract: The KM3NeT collaboration is building a deep-sea neutrino observatory in the Mediterranean Sea equipped with thousands of glass spheres, hosting the so-called digital optical modules, with an instrumented volume of several cubic kilometers. Reliability of the components used in the construction of the detectors is of extreme importance as the deployed detection units, each one composed of 18 digital optical modules, will not be accessible for any kind of maintenance and the detector should be functional for a period longer than 10 years. This work presents the different reliability methods used in KM3NeT to assess and improve the reliability of the electronics housed in the Digital Optical Modules of KM3NeT.